Spread of multidrug-resistant clonal complex 271 of serotype 19F Streptococcus pneumoniae in Beijing, China: characterization of serotype 19F. (December 2013) - LI, Q. H.; YAO, K. H.; YU, S. J.; MA, X.; HE, M. M.; SHI, W.; YANG, Y. H.
SUMMARY We investigated the genetic structure of 120 isolates of serotype 19F Streptococcus pneumoniae from Chinese children with acute respiratory infections collected from 1997 to 2006, and 2010. All strains were susceptible to vancomycin and levofloxacin, and only five strains were not susceptible to penicillin. The non-susceptibility rate to cephalosporins increased from 1997 to 2010. Of 119 erythromycin-resistant strains, 60 carried both ermB and mefA genes. The percentage of clonal complex 271 (CC271) increased from 14·3% in 1997–1998 to 92% in 2010, whereas that of CC983 decreased from 64·3% to 0%. CC271 had a higher non-susceptibility rate to β-lactam antibiotics than CC983 and other CCs. The increased non-susceptibility rate to β-lactam antibiotics in serotype 19F pneumococci was found to be associated with the spread of the international resistant clone CC271 presumably caused by antibiotic pressure. Long-term surveys of serotype 19F S. pneumoniae are required to monitor CC prevalence and trends in antimicrobial resistance.